2016
DOI: 10.1016/s2214-109x(15)00215-6
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and its risk factors in Malawian children admitted to hospital with clinical pneumonia, 2001–12: a retrospective observational study

Abstract: Summary Background Few studies have reported long-term data on mortality rates for children admitted to hospital with pneumonia in Africa. We examined trends in case fatality rates for all-cause clinical pneumonia and its risk factors in Malawian children between 2001 and 2012. Methods Individual patient data for children (<5 years) with clinical pneumonia who were admitted to hospitals participating in Malawi’s Child Lung Health Programme between 2001 and 2012 were recorded prospectively on a standardised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 27 publications
6
72
1
Order By: Relevance
“…As mentioned above, the additional counselling in patients on protease inhibitor-based second-line treatment might have slightly biased this finding. Girls were more vulnerable to virologic failure and the development of HIV-DRM for reasons that could not be explained in the framework of this study, but indeed sex inequalities were also found in other recent studies from East Africa [42]. …”
Section: Discussionsupporting
confidence: 71%
“…As mentioned above, the additional counselling in patients on protease inhibitor-based second-line treatment might have slightly biased this finding. Girls were more vulnerable to virologic failure and the development of HIV-DRM for reasons that could not be explained in the framework of this study, but indeed sex inequalities were also found in other recent studies from East Africa [42]. …”
Section: Discussionsupporting
confidence: 71%
“…Clinical data was collected as part of routine care by healthcare workers using the standard CLHP inpatient case report forms [6]. Variables collected included: demographics, immunization status, past medical history, history of present illness, vital signs, anthropometrics, clinical exam findings on admission, HIV and malaria status, chest radiograph findings, and treatment course.…”
Section: Methodsmentioning
confidence: 99%
“…Variables collected included: demographics, immunization status, past medical history, history of present illness, vital signs, anthropometrics, clinical exam findings on admission, HIV and malaria status, chest radiograph findings, and treatment course. HIV and malaria testing, while recommended, were inconsistently available [68]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations